2018
DOI: 10.4103/jrms.jrms_102_18
|View full text |Cite
|
Sign up to set email alerts
|

Rare histological subtype of pulmonary artery intimal sarcoma diagnosed by multidisciplinary approach

Abstract: Pulmonary artery intimal sarcoma (PAS) is a rare mesenchymal tumor mostly diagnosed in middle-aged women. In a 63-year-old female, the radiological findings showed cavitation in the left upper lobe of the lung and infiltrative tumor mass around the left pulmonary artery. PAS consisted of small, round tumor cells with about 80% of mitotic activity and with myxoid background and specific immunoprofile and diagnosed as undifferentiated sarcoma with round cell features type. The final diagnosis of PAS was establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Several investigators have reported that pulmonary artery sarcoma has MDM2 amplification and PDGFRα overexpression in PAS 16,22. The MDM2-p53 pathway is strongly associated with the tumorigenesis of pulmonary artery intimal sarcomas 23,24. Tovar C et al offered preclinical evidence that the MDM2 small-molecule antagonist RG7112 inhibited human tumors through p53 signaling 25.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported that pulmonary artery sarcoma has MDM2 amplification and PDGFRα overexpression in PAS 16,22. The MDM2-p53 pathway is strongly associated with the tumorigenesis of pulmonary artery intimal sarcomas 23,24. Tovar C et al offered preclinical evidence that the MDM2 small-molecule antagonist RG7112 inhibited human tumors through p53 signaling 25.…”
Section: Discussionmentioning
confidence: 99%